Coronary vasodilation by the use of sublingual nitroglycerin using 64-slice dual-source coronary computed tomography angiography. Issue 3 (March 2015) - Okada, Munemasa; Nakashima, Yoshiteru; Nomura, Takafumi; Miura, Toshiro; Nao, Tomoko; Yoshimura, Masayuki; Sano, Yuichi; Matsunaga, Naofumi
Abstract Background Sublingual nitroglycerin capsules or spray is routinely used to treat anginal attacks and to maximally dilate the epicardial coronary arteries during coronary angiography. These dilated coronary vessels have an advantage, but increased heart rates were disadvantageous for coronary computed tomography angiography (CTA). Purpose The influence of applying nitroglycerin was analyzed regarding the coronary diameter, coronary luminal attenuation, evaluable number of coronary segments, heart rate (HR), HR variability, the optimal reconstruction phase, and image scoring of CTA in the same patients using a 64-slice dual-source CT. Methods and subjects Fifty-two patients with atypical chest pain underwent coronary CTA before and after the administration of sublingual nitroglycerin without heart rate control. The coronary diameter and luminal attenuation were measured on short-axial images in each coronary segment. The coronary vasodilation ratios (VRs) were calculated from the coronary diameters at the same location before and after the use of nitroglycerin. The local institutional review board approved this study and written informed consent was obtained from all the patients. Results No significant differences were noted in the HR variability or optimal reconstruction phase, despite an increase in HR after the use of nitroglycerin. Nitroglycerin significantly enlarged the coronary artery diameter, and VRs of each coronary segment ranged from 7.54% to 22.26%. As compared with baseline coronary diameter, VRs of minor segments (16.91%) were significantly larger than those of major segments (11.35%), and the magnitude of VR correlated with the baseline coronary diameter (r = −0.48, p < 0.001). Coronary luminal attenuation significantly increased due to additional administration of contrast material after the use of nitroglycerin (p < 0.01), but no significant difference was noted in the image quality after the use of nitroglycerin. Conclusion Sublingual nitroglycerin significantly enlarged the coronary diameters, especially in peripheral small coronary arteries, and increased the evaluable number of coronary segments on coronary CTA.